Restoring Soil Fertility on Degraded Lands to Meet Food, Fuel, and Climate Security Needs via Perennialization - Mosier, Samantha; Córdova, S. Carolina; Robertson, G. Philip (Frontiers in Sustainable Food Systems, 2021)
A continuously growing pressure to increase food, fiber, and fuel production to meet worldwide demand has put severe pressure on soil resources. Abandoned, degraded, and marginal lands with large agricultural constraints – many still used for agricultural production – result from inappropriately intensive management, poor soil conservation measures, and climate change. Continued use for agricultural production requires the increased use of external inputs such as fertilizers and herbicides, which further exacerbates soil degradation and impedes nutrient recycling and retention. Growing evidence suggests that degraded lands have a large potential for restoration, perhaps most effectively via perennial cropping systems that can simultaneously provide multiple additional ecosystem services including continued production. Here we synthesize the advantages of and potentials for using perennial vegetation to restore soil fertility on degraded croplands. We highlight alternative management strategies, barriers to adoption, and potential solutions in order that cropland restoration might help to meet future food security needs.